Recommendations to government and all of society for a collaborative multi-stakeholder initiative for tackling malnutrition in a pandemic era in India - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Nutrition stakeholders endorsed and supported a Commitment to Action, which outlines areas of action to maintain and accelerate India’s progress on malnutrition in the context of the COVID-19 pandemic.